Digital Literacy Comics as an Innovative Learning Medium in Indonesian Language Instruction at Elementary School - Dewa Ayu Meitha Dwipayanti; Maria Goreti Rini Kristiantari; Anak Agung Ayu Dewi Sutyaningsih (Universitas Pendidikan Ganesha, 2025)
The limitations of engaging and contextual learning media remain a challenge in Indonesian language instruction at the elementary level. This study aimed to develop and evaluate a digital literacy based comic that is effective in enhancing students’ conceptual understanding of folktales. The research employed a Research and Development (R&D) design using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Participants included elementary students involved in product trials. Data were collected through expert validation (content, instructional design, and media), individual trials, small-group trials, and student comprehension tests. Descriptive quantitative analysis assessed the media’s validity, practicality, and effectiveness, while a t-test examined its impact on learning outcomes. Results showed that the digital comic achieved average validation scores above 90%, was practical, and effectively improved both understanding and student engagement. These findings confirm that the integration of visual, narrative, and interactive elements not only enhances literacy and reading motivation but also strengthens moral understanding and critical thinking skills. The implication is that digital literacy-based comics can serve as an innovative, interactive, and contextual instructional model, supporting literacy development, character building, and 21st-century competencies among elementary students.